Corporate social responsibility in the body shop (no. 5. Jln. USJ 10/1c, Subang Jaya) / Roziah Md. Salleh - Md. Salleh, Roziah (1997)
The purpose of this research is to identify the activities implemented by The Body Shop in respect to the social responsibility. 6 aspects were discussed and analysed to integrate and link the organisation with social responsibility. The aspects are in terms of employment, consumerism, public, environment, animal endangered and the activities' contribution to the company . As The Body Shop is a franchising company, the franchisee in Malaysia was chosen to be analysed. The research was conducted in Rampai Niaga Sdn. Bhd. that situated in USJ, Subang Jaya. Data have been collected through primary data such as interview with upper management, questionnaires to the staffs and public and observations and secondary data by examining documents used internally such as the company's mission and vission and others. The 6 aspects are the findings of the research. These aspects are used to achieve the research's objectives. These aspects or issues are selected as they are related to corporate social responsible and the implementation of the activities will indicate the practice of social responsibility in Malaysia.